The effect of time and temperature variations on the hydrolysis of sargassum muticum using microwave irradiation in the synthesis of bioethanol as renewable energy - Patrisius Maryanto Bria; Mikson Nahak; Sefrinus Maria Dolfi Kolo (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2024)
Consumption of fuel oil and the increasing population are increasing daily. The high level of energy consumption results in the oil supply reserves in the earth's bowels being depleted and will run out for the next few years. Bioethanol is ideal for replacing fossil energy because it has renewable, environmentally friendly, and renewable properties. Sargassum muticum can be converted into bioethanol because it contains monosaccharide carbohydrates such as glucose, galactose, and mannose and polysaccharides such as xylan, galactan, and mannan. The carbohydrate content of Sargassum muticum can be converted to bioethanol through a chemical hydrolysis process using a 3 % sulfuric acid catalyst and fermented with the help of Saccharomyces cerevisiae yeast with a 10 % inoculum for 6 days. The reducing sugar obtained from the hydrolysis process was analyzed by the DNS method using a UV-Vis spectrophotometer. Ethanol levels were analyzed qualitatively using potassium dichromate and quantitatively using a hand refractometer. The conversion of Sargassum muticum resulted in a reducing sugar content of 92.90 g/L at a temperature of 250 °C and a hydrolysis time of 60 minutes. The bioethanol content obtained from the fermentation of the hydrolyzed glucose was 42.32 %.